Database of Active Faults in Slovenia: Compiling a New Active Fault Database at the Junction Between the Alps, the Dinarides and the Pannonian Basin Tectonic Domains - Atanackov, Jure; Jamšek Rupnik, Petra; Jež, Jernej; Celarc, Bogomir; Novak, Matevž; Milanič, Blaž; Markelj, Anže; Bavec, Miloš; Kastelic, Vanja (Frontiers in Earth Science, 2021)
We present the compilation of a new database of active faults in Slovenia, aiming at introducing geological data for the first time as input for a new national seismic hazard model. The area at the junction of the Alps, the Dinarides, and the Pannonian Basin is moderately seismically active. Between 1000 AD and the present about a dozen Mw>5.5 earthquakes have occurred across the national territory, four of which in the instrumental era. The relative paucity of major earthquakes and low to moderate fault slip rates necessitate the use of geologic input for a more representative assessment of seismic hazard. The rich tectonic history of the region has resulted in complex regional structure making conclusive identification of active faults difficult. Additionally, overall high rates of erosion, denudation and slope mass movement processes with rates up to several orders of magnitude larger than fault slip rates obscure the surface definition of faults and traces of activity, making fault parametrization difficult. The presented database includes active, probably active and potentially active faults with trace lengths >5 km, systematically compiled and catalogued from a vast and highly heterogeneous dataset. Input data was mined from published papers, reports, studies, maps, unpublished reports and data from the Geological Survey of Slovenia archives and dedicated studies. All faults in the database are fully parametrized with spatial, geometric, kinematic and activity data with parameter descriptors including data origin and data quality for full traceability of input data. The input dataset was compiled through an extended questionnaire and a set of criteria into a homogenous database. The final database includes 96 faults with 240 segments and is optimized for maximum compatibility with other current maps of active faults at national and EU levels. It is by far the most detailed and advanced map of active faults in Slovenia.